An online curriculum in movement disorders for neurology housestaff. (2020) - Schaefer, Sara M.; Vadlamani, Lina; Juthani, Prerak; Louis, Elan D.; Patel, Amar; Tinaz, Sule; Rodriguez, Ana Vives; Moeller, Jeremy J.
Abstract: Introduction: In many neurology residency programs, outpatient neurology subspecialties are underrepresented. Trainee exposure to these subspecialties, including movement disorders, is limited by paucity and variability of clinical experiences. We designed a structured educational tool to address this variability and allow for standardization of elements of movement disorders teaching. Methods: We designed and implemented a web-based curriculum in movement disorders for neurology housestaff, in order to improve participant knowledge. The curriculum includes an introduction with a structured framework for the description of abnormal movements and 10 interactive modules focusing on common movement disorders. The curriculum was piloted with nine neurology housestaff at Yale-New Haven Hospital. Evaluation of the curriculum was performed using pre- and post-tests, a survey, and semi-structured interviews. Results: The mean pre-test score was 0.7 (±0.19), and the mean post-test score was 0.95 (±0.05) ( t = 3.27). Surveys demonstrated mean Likert values >4/5 for all questions in all categories (knowledge acquisition, quantity, enthusiasm and technical). Semi-structured interviews revealed the following themes: 1) the modules increased participant comfort with the topic, 2) the format was engaging, and 3) the curriculum accommodated different learning styles. All participants remarked that the structured framework was a particular strength. Conclusion: We have created, implemented, and evaluated a foundational curriculum in movement disorders for neurology trainees, using readily-available technology. Housestaff responded positively to the curriculum, both in terms of content and format. This curriculum can be implemented in a variety of educational settings, as a central component of a standardized approach to movement disorders teaching. Highlights: Neurology housestaff find interactive, online modules to be an acceptable and engaging supplement to their training. Neurology housestaff learn from online modules as demonstrated by survey and by pre- and post-testing. Neurology housestaff respond well to simple algorithms to approach movement disorders.